Changes in the Biophysical Properties of the Cell Membrane Are Involved in the Response of Neurospora crassa to Staurosporine - Santos, Filipa C.; Lobo, Gerson M.; Fernandes, Andreia S.; Videira, Arnaldo; de Almeida, Rodrigo F. M. (Frontiers in Physiology, 2018)
Neurospora crassa is a non-pathogenic filamentous fungus widely used as a multicellular eukaryotic model. Recently, the biophysical properties of the plasma membrane of N. crassa conidia were thoroughly characterized. They evolve during conidial germination at a speed that depends on culture conditions, suggesting an important association between membrane remodeling and the intense membrane biogenesis that takes place during the germinative process. Staurosporine (STS) is a drug used to induce programmed cell death in various organisms. In N. crassa, STS up-regulates the expression of the ABC transporter ABC-3, which localizes at the plasma membrane and pumps STS out. To understand the role of plasma membrane biophysical properties in the fungal drug response, N. crassa was subjected to STS treatment during early and late conidial development stages. Following 1 h treatment with STS, there is an increase in the rigidity of the more ordered, sphingolipid-enriched, domains in the plasma membrane of conidia. This leads to higher fluidity in other membrane regions. The global order of the membrane remains thus practically unchanged. Significant changes in sphingolipid-enriched domains were also observed after 15 min challenge with STS, but they were essentially opposite to those verified for the 1 h treatment, suggesting different types of drug responses. STS effects on membrane properties that are more dependent on ergosterol levels also depend on the developmental stage. There were no alterations on 2 h-grown cells, clearly contrasting to what happens at longer growth times. In this case, the differences were more marked for longer STS treatment, and rationalized considering that the drug prevents the increase in the ergosterol/glycerophospholipid ratio that normally takes place at the late conidial stage/transition to the mycelial stage. This could be perceived as a drug-induced development arrest after 5 h growth, involving ergosterol, and pointing to a role of lipid rafts possibly related with an up-regulated expression of the ABC-3 transporter. Overall, our results suggest the involvement of membrane ordered domains in the response mechanisms to STS in N. crassa.